The impact of puberty on the onset, frequency, location, and severity of attacks in hereditary angioedema due to C1-inhibitor deficiency: A survey from the Italian Network for Hereditary and Acquired Angioedema (ITACA) - Mauro Cancian; Paola Triggianese; Stella Modica; Francesco Arcoleo; Donatella Bignardi; Luisa Brussino; Caterina Colangelo; Ester Di Agosta; Davide Firinu; Maria Domenica Guarino; Francesco Giardino; Marica Giliberti; et al. (Frontiers Media S.A., 2023)
IntroductionHereditary angioedema due to C1-inhibitor deficiency is influenced by hormonal factors, with a more severe course of disease in women. Our study aims to deepen the impact of puberty on onset, frequency, location and severity of attacks.MethodsRetrospective data were collected through a semi-structured questionnaire and shared by 10 Italian reference centers of the Italian Network for Hereditary and Acquired Angioedema (ITACA).ResultsThe proportion of symptomatic patients increased significantly after puberty (98.2% vs 83.9%, p=0.002 in males; 96.3% vs 68,4%, p<0.001 in females); the monthly mean of acute attacks was significantly higher after puberty, and this occurred both in females (median (IQR) = 0.41(2) in the three years before puberty vs 2(2.17) in the three years after, p<0.001) and in males (1(1.92) vs 1.25(1.56) respectively, p<0.001). The increase was greater in females. No significant differences were detected in attack location before and after puberty.DiscussionOverall, our study confirms previous reports on a more severe phenotype in the female gender. Puberty predisposes to increased numbers of angioedema attacks, in particular in female patients.